Development and Validation of Digital Photo Series for the Teaching of BT in Ilorin, Nigeria - Ebenezer Omolafe Babalola; Charity H. M. Boor; Gboyega Ayodeji Aladesusi; Mariam Adenike Shomoye (Universitas Pendidikan Indonesia (UPI), 2021)
The essence of basic technology (BT) in the secondary school curriculum is to assist learners to develop an interest in technology and introduce students to the basic rudiment of technology. Thus, BT teachers must use relevant instructional media that would help in achieving the aims of BT in secondary. This study developed and validated a digital photo series to teach BT concepts in upper basic schools in the Ilorin metropolis. The study adopted a design and development model type. Five BT teachers and three educational technology experts were randomly selected to participate in the study. Three research instruments were used in this study, a developed digital photo series on the BT concept, an educational technology expert rating guide, and a subject content validation questionnaire. Digital photo series was successfully developed to teaching upper BT. Educational technology experts agreed that the developed digital photo series satisfied the required expectation. The cost for developing digital photo series was determined. The study concluded that the digital photo series is a powerful instructional tool that can enhance the teaching of BT in Nigeria. The findings imply that schools should adopt the use of digital photo series in the teaching and learning of BT to concretize learning contents and increase students’ performance.